Effect of mechanical stresses on the domain structure of barium titanate single crystals - V. V. Borodina; S. O. Kramarov (Российский технологический журнал)
This review article summarizes the material of years of research on the impact of mechanical stresses on the domain structure of multiaxhetoelectrics using the example of barium titanium monocrystals. Since the discovery of the ferroelectric properties of barium titanate in 1944, this material has been the subject of comprehensive investigation as the first practically important and perhaps the most famous ferroelectric. The domain structure of barium titanate is sensitive to mechanical stresses arising both from simple uniaxial compression and from point impacts by local mechanical loading. Mechanical stress applied to a ferroelectric crystal may have a significant effect on dielectric and piezoelectric properties. In particular, 90-degree domain switching is possible under the influence of stresses. The most interesting experimental results are obtained in the study of elastoplastic processes in BaTiO 3 originating from local mechanical stresses. The following features are found and studied: development of strained region around the point of application of the load; “internal” 90-degree domain that does not extend to the crystal surfaces and does not close upon other domains; the growth of 90-degree domains under the influence of residual mechanical stresses; growth of cracks along charged 90-degree domain walls. The notions of “ferroplastic effect” (crystal deformation due to the formation of 90-degree ferroelectric domains) and “ferromechanical effect” (crack formation and growth along charged 90-degree domain walls) are introduced. The hypothesis of a significant role of oxygen vacancies in the processes of 90-degree domain reorientation was put forward and experimentally confirmed. In particular, an increase in the concentration of oxygen vacancies by reducing annealing of barium titanate single crystals creates more favorable conditions for the appearance of an "internal" 90-degree domain under local mechanical load. The study of the mechanisms governing the formation of a domain structure in ferroelectric crystals remains an important problem of modern materials science.